Ecolinguistics and Media: Analyzing the Semiotic Framing of Environmental Issues in Pakistani Newspapers (The Journal of Cultural Perspectives, 2024)
The study examined how through certain semiotic choices, Pakistani English newspaper 'The Dawn' presented environmental issues to their readership, in a particular manner. Employing a purposive sampling technique, ten pictorials addressing environmental issues were downloaded from internet archives published from 2019 to 2023 in the said newspaper. Kress and van Leeuwen's theory of visual grammar (2006) and Arran Stibbe's theory on ecolinguistics (2015) were leveraged as theoretical frameworks. The researchers aimed to uncover the semiotic repertoire employed to depict environmental challenges. A qualitative analysis was carried out of each pictorial, the major areas addressed were the national and international economic woes and environmental troubles stemming from global warming and climate change. Moreover, these issues, the deleterious effects they entail and the urgent measures required were highlighted using various metaphors, framing and salience. The stakeholders are recommended to initiate and foster environmentally friendly practices through recognition, strengthening environmental regulations, and using media to raise awareness and inspire collective action. To ensure a safe future for us and our progeny raising awareness and being proactive to the environmental issues is indispensable.